An Analysis of Effectiveness and Efficiency of Village Financial Management in Serdang District, the Differences on the Performance of Institutions - Anju Bhernadetha Nainggolan (International Journal of Economics (IJEC), 2022)
This research was conducted in Sei Rampah District, precisely in the Village of Silau Rakyat which aims to find out how is the financial performance of the village based on the concept of value for money by measuring the level of effectiveness and efficiency APBDesa on agency performance in Sei Rampah Subdistrict. This study uses a quantitative design. The sample in this study amounted to 40 people. The data used in this study are primary data obtained through questionnaires, interviews, field observations and documentation. Data processing and statistical analysis used SPSS version 1 8.0 with a significance level of 0.05. The results of the validity and reliability test, all research instruments are valid, valid and reliable. The data analysis technique used is the coefficient of determination test (R2) through multiple linear regression test. The results of statistical tests in this study stated that the variables of effectiveness and efficiency of village financial management were able to explain the performance of village financial management agencies by 1.5 % , the remaining 98.5% were influenced or explained by other variables not included in this study . From the Coefficients table a multiple linear regression equation is obtained Y = 30.725 + 0.019 X1 - 0.227X2 + e. Constant (a) = 30.725, if the effectiveness and efficiency of village fund budget management, it is assumed that there is no change (constant) then the value of Y (performance of agencies) is 30.725 Partially.